Effect Of Nadi Shuddhi Pranayama On Anxiety, Stress, Depression, Quality Of Life, And Physiological Markers In Breast Cancer Patients: A Randomised Controlled Trial - J, Jeevan (International Research Journal of Ayurveda & Yoga, 2026)
Background:Breast cancer patients frequently experience elevated anxiety, psychological stress, depression, and significant physiological disturbances as consequences of both the disease and its treatment. Nadi Shuddhi pranayama (alternate nostril breathing), a foundational yogic breathing technique, has demonstrated capacity to modulate autonomic nervous system function and improve psychological well-being. However, its isolated therapeutic effects in breast cancer populations, encompassing both psychological and physiological parameters, have not been rigorously established through randomised controlled methodology. Objective:To evaluate the effect of a structured 12-week Nadi Shuddhi pranayama intervention on anxiety, stress, depression, quality of life, and selected physiological markers (heart rate, respiratory rate, blood pressure, and oxygen saturation) in breast cancer patients. Methods:Fifty breast cancer patients were randomly allocated to an intervention group (n=25) receiving daily Nadi Shuddhi pranayama for 12 weeks, or a control group (n=25) receiving standard oncological care only. Psychological outcomes were assessed using the Depression Anxiety Stress Scale-42 (DASS-42) and Quality of Life Scale (QOLS). Physiological markers including heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), respiratory rate (RR), and peripheral oxygen saturation (SpO2) were recorded at baseline and post-intervention. Results:The intervention group demonstrated statistically significant improvements across all psychological parameters: anxiety (DASS-42 severe category: 100% pre vs. 16% post), stress (severe: 24% pre vs. 8% post), and depression (severe: 76% pre vs. 12% post). QOLS scores improved from a mean of 2.88 to 3.91 (p<0.001). Physiological markers showed significant reductions in HR (84.2 to 72.6 bpm), SBP (134.4 to 122.8 mmHg), DBP (88.1 to 79.3 mmHg), and RR (18.6 to 14.2 breaths/min), with a significant increase in SpO2 (96.1% to 98.4%). The control group showed no statistically significant changes in any parameter. Conclusion:Nadi Shuddhi pranayama is an effective, safe, and accessible complementary intervention that significantly improves psychological well-being, quality of life, and key physiological markers in breast cancer patients. Its integration into oncological supportive care is strongly recommended.